The Defense Mechanisms and The Behaviour of The Criminal Mind - Oruç, Derya (2023)
This book examines the relationship between defense mechanisms and the behaviors of a criminal mindset. The author explores the reasons behind a criminal mindset and how criminals utilize defense mechanisms, while also considering the impact of the superego and object relations on personality disorders. The book also delves into narcissistic personality disorder and extensively discusses the defense mechanisms of individuals with this disorder. The representations of narcissistic characters in literary texts are also examined, with examples such as Robert Browning's \"The Last Duchess,\" William Shakespeare's \"Othello,\" and Oscar Wilde's \"The Picture of Dorian Gray\" being analyzed. This book is adapted from the thesis titled \"Defense Mechanisms and the Behaviors of a Criminal Mindset,\" written under the supervision of Prof. Dr. Mehmet Oğuz Cebeci from Yeditepe University's Institute of Social Sciences.